Avaliação da torta de soja como fonte proteica para ruminantes: digestibilidade e oferta de proteína metabolizável em ovinos - Vargas, Mauro Emilio Alfredo (2023)
The objective of this study is to evaluate the impact of the inclusion of soybean cake (TS) in complete diets (TMR) offered to sheep on digestive and metabolic parameters in comparison to protein sources commonly used in the feeding of two ruminants and with known nutritional properties: farelo soybean (FS), with high rumen degradability, and distilled dry residue with solvents (DDG), with low rumen degradability. Five castrated male Hampshire Down lambs (35 ± 5 kg live weight), surgically implanted with ruminal probes and ''T'' type cannulas in the proximal duodenum, forams used in a double layout Latin Square 3 × 3 incomplete, with an additional period. The experimental diets were isoproteic and formulated with 60% by volume and 40% of concentrate, dry matter (DM) basis. As voluminous, mill silage was used and for formulation two concentrates were used ground mill, mineral core, common salt and one of the following protein sources: FS, TS or DDGs. The higher consumption of NDF was observed for diets with DDGs (P = 0.050). A diet with FS showed apparent and true OM digestibility higher than the DDGs (P<0.050) and, a diet with TS, showed intermediate values to the other treatments. A tendency of lower apparent N digestibility was observed for the treatment with DDGs (P=0.135). Overall, the inclusion of DDGs in TMR reduced urinary N excretion (P= 0.015) and, as a consequence, tended to increase N retention (P=0.141) and increased N utilization efficiency (P< 0.050) in comparison with diets with TS and FS. All treatments will cause a decrease in ruminal pH after each morning and afternoon meal (P < 0.001). TS and FS resulted in higher rumen concentration of amonia in comparison with DDGs (P < 0.001). The duodenal flow of MO, total N, α-amino N, Pmc and residual N were similar in all treatments. In conclusion, most of the variables analyzed in this study will indicate that the nutritional properties of TS are similar to those of FS.